Self-care in older people with functional deficit: needs of long-term care - Ramos, Ana (2018)
The group of 65-year-olds is becoming more numerous and with greater needs for health care. So, is necessary the reflection about new models of provision, organization, and allocation of health resources [1]. According to the United Nations Organization, 2015 [2], in 2050 elderly people will reach two million people (20% of the world’s population), what mean that the number of people over 60 years old will exceed a population of young people under 15 years.